Simulation Model to Predict the Performance of UASB Reactor (Asian Journal of Applied Sciences, 2017)
This paper explored the applicability of multiple linear regression model to predict the performance of an Up-flow Anaerobic Sludge Blanket Reactor (UASBR) for treating effluents of sugar, sago and dairy. UASBR was run at continuous mode with different combinations of influent COD and influent flow rate. The flow rates were maintained at 4.8, 12.0, 14.4, 18.0 and 24.0 l/day corresponding to Hydraulic Retention Time (HRT) of 5.21, 2.08, 1.39 and 1.04 respectively. The resulted upward velocity varied from 0.0064 to 0.031 m/hr. The experiment was run for continuous observations for COD, Volatile Suspended Solids (VSS) and biogas generation.Â  Data obtained on HRT, Volumetric Loading Rate (VLR), Organic Loading Rate (OLR) and VSS for treating sugar, sago and dairy effluents were used as independent parameters. Based on the data, regression equation was proposed for percentage removal efficiency of COD for each effluent. The proposed regression equations were proved to closely predict the performance of UASBR. Â Â